Acute brain injury and nanomedicine: sex as a biological variable - Simmons, Amberlyn; Mihalek, Olivia; Bimonte Nelson, Heather A.; Sirianni, Rachael W.; Stabenfeldt, Sarah E. (Frontiers in Biomaterials Science, 2024)
Sex as a biological variable has been recognized for decades to be a critical aspect of the drug development process, as differences in drug pharmacology and toxicity in female versus male subjects can drive the success or failure of new therapeutics. These concepts in development of traditional drug systems have only recently begun to be applied for advancing nanomedicine systems that are designed for drug delivery or imaging in the central nervous system (CNS). This review provides a comprehensive overview of the current state of two fields of research -nanomedicine and acute brain injury -centering on sex as a biological variable. We highlight areas of each field that provide foundational understanding of sex as a biological variable in nanomedicine, brain development, immune response, and pathophysiology of traumatic brain injury and stroke. We describe current knowledge on female versus male physiology as well as a growing number of empirical reports that directly address sex as a biological variable in these contexts. In sum, the data make clear two key observations. First, the manner in which sex affects nanomedicine distribution, toxicity, or efficacy is important, complex, and depends on the specific nanoparticle system under considerations; second, although field knowledge is accumulating to enable us to understand sex as a biological variable in the fields of nanomedicine and acute brain injury, there are critical gaps in knowledge that will need to be addressed. We anticipate that understanding sex as a biological variable in the development of nanomedicine systems to treat acute CNS injury will be an important determinant of their success.